Middle Ear Carcinoid Tumor: A rare case - Eng Siang Lee; Ing Ping Tang (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Introduction: Carcinoid tumor of the middle ear (ME) is exceedingly rare and thus its diagnosis is frequently delayed. It is also hard to differentiate between middle ear carcinoid from the middle ear adenoma. Definitive diagnosis is made by identifying neurosecretory tumor cells using immuno histochemistry and electron microscopy.  Case presentation: We report here a case of a carcinoid tumor observed in the middle ear (ME). The patient presented with right otalgia and ear bleed of one month duration.  Outcome: A lateral resection of the right temporal bone was performed. The patient's initial symptoms immediately improved after surgery, but facial palsy remained in the following months. No recurrence was noted after twelve months of follow-up. The patient is without recurrence of her disease to date.  Discussion: This case suggests the difficulties in distinguishing ME carcinoid tumors from other ME tumors.  Conclusion: This case suggests the difficulties in distinguishing ME carcinoid tumors from other ME tumors. High degree of clinical suspicion is required to consider middle ear adenomas, and carcinoid tumors. Reporting new cases would help to increase the awareness towards the disease.